2008
DOI: 10.1590/s0066-782x2008000600008
|View full text |Cite
|
Sign up to set email alerts
|

Insuficiência cardíaca descompensada na unidade de emergência de hospital especializado em cardiologia

Abstract: SummaryBackground: National studies on decompensated heart failure (DHF) are key to the understanding of this condition in our midst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 21 publications
(19 reference statements)
0
20
2
7
Order By: Relevance
“…The severity and characteristics of the patients in group B reinforce previous observations that patients with signs of cardiogenic shock, renal failure and Chagas disease with extensive myocardial damage, and those who are poorly oriented, have poorer progress in the group. (12,14,16) Although negative results for adherence to treatment were not found, the length of hospitalization for compensation of heart failure patients in this study was higher than that reported in the literature, a mean of nine days for severely ill patients. (15) It is known that the length of hospitalization for compensation of patients is an important aspect, since it implies costs of treatment.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The severity and characteristics of the patients in group B reinforce previous observations that patients with signs of cardiogenic shock, renal failure and Chagas disease with extensive myocardial damage, and those who are poorly oriented, have poorer progress in the group. (12,14,16) Although negative results for adherence to treatment were not found, the length of hospitalization for compensation of heart failure patients in this study was higher than that reported in the literature, a mean of nine days for severely ill patients. (15) It is known that the length of hospitalization for compensation of patients is an important aspect, since it implies costs of treatment.…”
Section: Discussioncontrasting
confidence: 77%
“…(14,19) Our study frequently found the combination of congestion and low output, in addition to isolated low output. Therefore, the need for vasoactive drugs and mortality were very common, in addition to prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 79%
“…At hospital admission, these patients predominantly exhibit congestive manifestations, [3,4] with hypervolemia accounting for 80.7% of hospitalizations due to decompensated HF. [5] Almost 50% of patients hospitalized with HF are readmitted within 90 days after hospital discharge and mortality rates increase with each readmission of these patients. [6] In view of the association between excessive sodium intake and fluid retention, restricted salt intake is the nonpharmacological self-care measure most commonly prescribed to patients with HF.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, those that refer to the treatment adherence, one of the main reasons for decompensated HF, are related in several studies (16) . The results of this study showed the selected ND of Readiness for Enhanced Self health Management, Ineffective Self health Management, Ineffective Family Therapeutic Regiment Management, which are aimed to the identify the responses of individuals and family about health problems related to HF.…”
Section: Discussionmentioning
confidence: 99%